Tingkat Kepatuhan Protokol Kesehatan Covid-19 pada Rumah Makan di Kecamatan Gubug Kabupaten Grobogan - Widyastuti, Laras; Pawenang, Eram Tunggul (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Based on the results of observations carried out on August 18, 2021 at 5 restaurants in Gubug District, the results were only one restaurant whose workers wore masks. Four restaurants have hand washing facilities. Five restaurants do not apply temperature checks. One restaurant that implements social distancing and disinfects. Methods: This type of research is Analytical Observation with a Cross Sectional design. The sampling technique is the total sampling technique. The total sample is 44 restaurant respondents. Research instruments in the form of questionnaires and observation sheets. Data were analyzed using Fisher's test. Results: Shows that there is a relationship between worker hygiene (p = 0.027), hand washing facilities (p = 0.001), and disinfection (p = 0.018) with the level of compliance with COVID-19 health protocols at restaurants in Gubug District, Grobogan Regency. There is no relationship between knowledge of business actors (p=0.456), knowledge of workers (p=1,000), temperature checks (p=0.075), and social distancing (p=0.083) with the level of compliance with COVID-19 health protocols at restaurants in the sub-district Gubug Grobogan Regency. Conclusion: The description of compliance with the COVID-19 health protocol in restaurants is mostly in accordance with applicable guidelines.